Influence of dry and wet environments during fiber laser processing of metallic substrate under a neoteric scan mode. (February 2023) - Panigrahi, Debasish; Patel, S.K.
Graphical abstract: D-PLMMP and W-PLMMP by LO-OLPS. Highlights: A linear orbit in orbit laser beam positioning strategy (LO-OLPS) is introduced in PLMMP for fabrication of micro-channels under the neoteric parametric combinations. A study under the dry and wet environments was accomplished. Material ablation and dimensional characteristics were reported against D-PLMMP. Surface morphology, elemental analysis, phase quantifications, functional group identification, and micro-hardness studies akin to crystallite size and lattice strain were scrutinized under two environments. Abstract: The demand for improved machining productivity and good surface characteristics is of utmost importance in laser micro-machining. This research asserts the pulsed laser micromachining process (PLMMP) to fabricate micro-channels on Fe-Cr-Ni enriched superalloy for heat exchanger applications in the marine industry. As PLMMP is one of the exacting manufacturing processes, this study intends to improve it by introducing a linear orbit-in-orbit laser beam positioning strategy (LO-OLPS) to generate micro-channels. The core goal of this research is to raise awareness of some unique parameters and their potential consequences on the major characteristics, like dimensionality, material ablation, and surface irregularities. By tweaking the MDPSS fiber laser scan modes, the current method was examined under dry and wet conditions as a distinct industrial potential. Apart from these, metallography analysis, including phase quantifications, elemental analysis, surface morphology, functional group identification, and micro-hardness (µH) studies akin to crystallite size (D) and lattice strain (ε), were scrutinized on D-PLPS and W-PLPS. In both conditions, the obtained γ-phase is similar to the base substrate, but in D-PLPS, an additional peak named CrO2 was obtained from XRD results. D values are lower in dry (D-PLPS) than in wet pulsed laser processed surface (W-PLPS), while µH and ε values are higher in D-PLPS. EDS results revealed that element like oxygen was found to be more abundant on the D-PLPS than on the W-PLPS, while carbon content is slightly copious in the case of W-PLPS compared to the D-PLPS. Furthermore, both environments had molecular bond displacement relative to the base material.